The Unspoken Rules: Secrets To Starting Your Career Off Right - Ng, Gorick (Boston Harvard Business Review Press, 2021)
"What will separate you from the rest early in your career? The ability to take ownership, manage expectations, navigate people dynamics, and communicate professionally-skills that school doesn't teach. Most career guides assume that you already know how the working world works. But if you're starting your very first job or taking a job in a new company, you might not know all the unspoken rules that determine who gets ahead and who doesn't. In The Unspoken Rules, you'll learn the basic workplace skills necessary for success. From the author: "Why didn't anyone ever tell me this?! I've lost count of the number of times I've asked myself this question. As the son of a single mother who dropped out of school at the age of twelve to work in a sewing-machine factory, I missed the lesson on the unspoken rules of the professional workplace. Instead, I learned my lesson the hard way-through trial and error. Now I'm on a mission to discover and decode the unspoken rules of work and share them with others. Over the last four years, I've interviewed over five hundred interns, early career professionals, managers, and executives, from HR to finance, law firms to tech companies, across the globe. My conversations revolved around three key topics: What are the most common mistakes early-career professionals make at work? What would you do differently if you could relive your first years on the job? What do you think separates top performers from mediocre ones? After testing the advice I gathered from these hundreds of interviews, I started coaching other early-career professionals. Now I'm distilling everything I've learned into a step-by-step guide called The Unspoken Rules. We all have what it takes to be a top performer. It begins with mastering the unspoken rules.""--
Includes bibliographical references and index.
Keywords: Career development; Success in business